2011
DOI: 10.1107/s0108768111018544
|View full text |Cite
|
Sign up to set email alerts
|

CaSeO4·0.625H2O – water channel occupation in a bassanite related structure

Abstract: Calcium selenate subhydrate, CaSeO(4)·0.625H(2)O, was prepared by hydrothermal conversion of CaSeO(4)·2H(2)O at 463 K. From the single crystals obtained in the shape of hexagonal needles, 50-300 µm in length, the crystal structure could be solved in a trigonal unit cell with space group P3(2)21. The cell was confirmed and refined by high-resolution synchrotron powder diffraction. The subhydrate was characterized by thermal analysis and Raman spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The single-crystal structure solution of CaSeO 4 Á0.625H 2 O (Fritz et al, 2011) demonstrated that water contents higher than 0.5H 2 O are possible in bassanite analogous structures, although the unit cell of the selenate is 10% larger compared with the sulfate. As a consequence of the smaller unit-cell volume of CaSO 4 Á0.5H 2 O the distances between water molecules are short.…”
Section: Introductionmentioning
confidence: 99%
“…The single-crystal structure solution of CaSeO 4 Á0.625H 2 O (Fritz et al, 2011) demonstrated that water contents higher than 0.5H 2 O are possible in bassanite analogous structures, although the unit cell of the selenate is 10% larger compared with the sulfate. As a consequence of the smaller unit-cell volume of CaSO 4 Á0.5H 2 O the distances between water molecules are short.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there is not a previous study of Raman or infrared spectroscopy of CaSeO 4 . In contrast, there are some reports about the Raman and infrared spectra of CaSeO 4 · n H 2 O. , On the other hand, there are some reports of vibrational properties under pressure for similar compounds to CaSeO 4 , such as CaSO 4 and PbSO 4 , which identified the phase transitions driven by pressure with the help of Raman spectroscopy. Here, the frequencies of the Raman and IR active modes for the Cmca , monazite, scheelite, and AgMnO 4 -type structures have been calculated as well as their pressure dependences.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Similarly, the existence of only one bending mode at 1615 cm -1 could be correlated to the quasi-equivalent nature of the water molecules in the rhabdophane structure. Also, as in the case of churchite, a parallel can be drawn [43] but without investigating the typical wavenumber range of water molecules vibration. In these conditions, the FTIR and Raman data collected in this study for GdPO4•0.667H2O rhabdophane can be considered as a potential firstbasis approach to forecast the spectral characteristics of water in these compounds.…”
Section: Water Moleculesmentioning
confidence: 99%